Surviving a shark attack (on land) : overcoming betrayal and dealing with revenge - Schlessinger, Laura (New York : Harper, 2011)
A popular radio talk-show host shows readers how to survive enemies--traitors, backstabbers, and saboteurs--at work and at home.
Keywords: Betrayal; Revenge; Interpersonal conflict